(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the short-term outcomes of right hepatectomy for intrahepatic cholangiocarcinoma. Subject and method: This was a retrospective descriptive study of the cases who underwent right hepatetomy for intrahepatic cholangiocarcinoma at Department of hepatobiliary and pancreatic surgery in National cancer hospital from March 2017 to November 2022. Result: Elective surgery was performed for 27 patients. The average age was 60.2 ± 11.2 years, sex ratio was 1.25 male per 1 female; 18.5% of cases had a history of hepatolithiasis; hepatitis B and hepatitis C related: 68.3%. Elevated of CA 19-9 and CEA levels were seen in 77.8% and 55.6% of cases respectively. Anatomical right hepatectomy has the majority (81.5%); regional lymphadenectomy was performed in 11.1% of cases. Most of patients had the solitary tumor (51.8%) with its size being larger than 5cm (63%). Postoperative pathology: cholangiocarcinoma (81.5%), lymph node metastases (11.1%), IIIA TNM staging (66.7%). The mean operation time was 166.3 ± 55.4 min. Postoperative complications have the majority in pleural effusion (22.2%) and liver failure (14.8%). The classification of complications according to Clavien – Dindo were: I (66.7%), II (18.5%), IIIa (14.8%). Conclusion: Right hepatectomy for intrahepatic cholangiocarcinoma is a feasible, safe and effective method.